2003
DOI: 10.1111/j.1523-1739.2003.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Landowners' Responses to an Endangered Species Act Listing and Implications for Encouraging Conservation

Abstract: Private landowners manage many rare species' habitats, yet research on their responses to species conservation legislation is scarce. To address this need, we examined private landowners' responses to the listing of the Preble's meadow jumping mouse (Zapus hudsonius preblei) as threatened under the U.S. EndangeredSpecies Act (ESA). We mailed a questionnaire designed to measure these responses to a sample of landowners. The adjusted response rate was 46% (n = 379). The questionnaire asked landowners whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(89 citation statements)
references
References 26 publications
1
86
1
1
Order By: Relevance
“…The distribution of benefits and burdens has been explored in great detail with numerous case studies. This is true even inside conservation literature, because we know the importance of landowner incentives and compensation schemes (see Farrier 1995, Brook et al 2003, Kreuter et al 2006, Muradian et al 2013). However, we know much less about the perceived fairness of conservation policy (Olive 2014, Pascual et al 2014 and even less about the importance of landowner recognition.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The distribution of benefits and burdens has been explored in great detail with numerous case studies. This is true even inside conservation literature, because we know the importance of landowner incentives and compensation schemes (see Farrier 1995, Brook et al 2003, Kreuter et al 2006, Muradian et al 2013). However, we know much less about the perceived fairness of conservation policy (Olive 2014, Pascual et al 2014 and even less about the importance of landowner recognition.…”
Section: Discussionmentioning
confidence: 97%
“…Kreuter et al (2006), for example, found that landowners in Colorado, Texas, and Utah generally disagreed with the notion that landowners should protect endangered species habitat without compensation from the public. Similarly, Brook et al (2003Brook et al ( :1641 found a positive correlation between landowners who thought they should not "bear financial responsibility" for conservation and those indicating that they managed their properties to minimize the chance of an endangered species occupying it. These studies have led to the conclusion that compensation would be fairer.…”
Section: Environmental Justice and The Esasmentioning
confidence: 99%
“…Landowners generally believe that they should be compensated for protecting at-risk or endangered species (Brook et al 2003, Kreuter et al 2006, Raymond and Olive 2008. Landowners showed a strong preference for increasing their profit.…”
Section: Discussionmentioning
confidence: 99%
“…To be acknowledged as a good farmer in the farming community in the UK, the appearance of the farm is important: straight planted crops, tidy ditches and managed hedges 28 . There is a fear among farmers of losing control over the land, and as a result of this fear 56% of US farmers would not allow a biological survey of their land to avoid the risk of having their land regulated 29 . Likewise, there is concern about the potential for official designation of endangered species on their land that may limit decisions in management.…”
Section: Description Of Farmers and Their Contextmentioning
confidence: 99%